2017
DOI: 10.1111/bjet.12579
|View full text |Cite
|
Sign up to set email alerts
|

Factors underlying students' decisions to use mobile devices in clinical settings

Abstract: University policies prohibiting use of mobile devices by medical students during clinical placements are contradicted by regular use by physicians. Consequently, many students use their mobile devices, which can be beneficial for learning but may put patient privacy at risk. This study explores the reasons underlying students' decisions about using mobile devices in clinical settings. We used a mixed‐methods sequential explanatory design involving a questionnaire and focus groups. Qualitative data from the que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…The same type of research on the use of new technology by successive medical student cohorts in the early stages of clinical courses had not been conducted before. However, our results were consistent with previous research findings [ 1 , 3 , 14 ]. Both previous research literature and our own previous research on the first cohort of medical students reported challenges in incorporating devices into clinical settings [ 12 , 16 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The same type of research on the use of new technology by successive medical student cohorts in the early stages of clinical courses had not been conducted before. However, our results were consistent with previous research findings [ 1 , 3 , 14 ]. Both previous research literature and our own previous research on the first cohort of medical students reported challenges in incorporating devices into clinical settings [ 12 , 16 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 94%
“…The uncertainty of patients’ reactions has not been the only major obstacle in adopting mobile technology in the clinical context. Students’ have also faced social barriers in the form of their device usage and online information seeking being construed as unprofessional behaviour and misinterpreted as personal use of social media by senior doctors and other healthcare professionals [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The same type of research on the use of new technology by successive medical student cohorts in the early stages of clinical courses had not been conducted before. However, our results were consistent with previous research ndings (1,3,15). Both previous research literature and our own previous research on the rst cohort of medical students reported challenges in incorporating devices into clinical settings (13,17,18,19).…”
Section: Discussionsupporting
confidence: 93%
“…They were also worried that using the device might deteriorate their communication with the patients (2,7,13,14). In addition, they feared that senior physicians and other health care professionals would construe their behaviour as unprofessional or misinterpret their online information seeking for personal communication on social media (13,14,15). The few studies exploring the patients' own perceptions of bedside usage of mobile devices reported positive attitudes among patients (6, 10, 12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation